Determination of inorganic radioiodines in 131I labelled compounds by means of instantaneous thin layer chromatography - Bianco de Salas, Gladys N.; Alvarez, J.; Mitta, Aldo Enrique (1972)
Fil: Bianco de Salas, Gladys N. Comisión Nacional de Energía Atómica; Argentina